Tinjauan Yuridis Penjatuhan Putusan Terhadap Eksepsi Kewenangan Relatif Dalam Mengadili Perkara Perzinahan (Studi Kasus Putusan Sela Nomor: 14/Pid.B/2023/PN Bli) - Ni Kadek Ayu Dwiyanti; I Made Minggu Widyantara; Kade Richa Mulyawati (Jurnal Analogi Hukum, 2025)
Exception is a form of objection or legal action that can lead to an interlocutory decision taken by a judge, usually in response to a challenge regarding his authority to adjudicate in court. The problem is 1) how the basis for determining relative authority in the decision of an adultery case is a case study of interlocutory decision Number 14/Pid.B/2023/PN Bli? and 2) how the ratio legis of the judge related to the authority to adjudicate in interlocutory decision Number 14/Pid.B/2023/PN Bli?. The purpose is to know and describe the basis for determining relative authority in the decision of an adultery case case study and the suitability of the judge's ratio legis related to the authority to adjudicate in Interlocutory Decision Number 14/Pid.B/2023/PN Bli. The method used is the normative law method. The relative authority to handle cases between two courts is determined by Law Number 8 of 1981 concerning Criminal Procedure Law (KUHAP), specifically articles 148 and 84. The judge's understanding of the interlocutory decision was that the Bangli District Court acknowledged the objection of the legal counsel stating that it did not have the authority of the case.